Flexural Behavior Analysis of Geopolymer Reinforced Concrete Beams Using Finite Element Method - Sela, Reynaldo Jeremy; Sumajouw, Dody M.J.; Mondoringin, Mieke R.I.A.J (Journal of Engineering, Electrical and Informatics, 2025)
This study aims to analyze and validate the flexural behavior of reinforced geopolymer concrete beams compared to conventional concrete using a numerical approach through the Finite Element Method (FEM) with ANSYS software. The simulations were based on geometric and material parameters from previous experimental studies, including those by Abraham et al. (2013), Dattatreya et al. (2011), and Ojha et al. (2022). The simulation results indicate that the load–deflection behavior, crack distribution patterns, and flexural capacity of geopolymer concrete beams are comparable to those of conventional concrete beams. Validation against experimental data shows small deviations in both ultimate load and maximum deflection, confirming the accuracy of the numerical model. Crack propagation in the flexural zone also demonstrates similar characteristics, suggesting that geopolymer concrete is a viable alternative structural material. This research contributes to the development of numerical modeling to support the implementation of geopolymer concrete in sustainable construction.